The Subject of Conceptual Mapping: Theological Anthropology across Brain, Body, and World - Kidd, Erin (Open theology, 2018)
Research in conceptual metaphor and conceptual blending-referred to collectively as "conceptual mapping"-identifies human thought as a process of making connections across fields of meaning. Underlying the theory of conceptual mapping is a particular understanding of the mind as embodied. Over the past few decades, researchers in the cognitive sciences have been "putting brain, body, and world back together again." The result is a picture of the human being as one who develops in transaction with her environment, and whose highest forms of intelligence and meaning-making are rooted in the body’s movement in the world. Conceptual mapping therefore not only gives us insight into how we think, but also into who we are. This calls for a revolution in theological anthropology. Our spirituality must be understood in light of the fact that we are embodied beings, embedded in our environment, whose identities are both material and discursive. Finally, using the example of white supremacy, I show how this revolution in understanding the human person can be useful for ethical reflection, and in thinking about sin and redemption.